By chance alone : a remarkable true story of courage and survival at Auschwitz - Eisen, Max (Hanover Square Press, 2020)
This autobiography of Canadian Max Eisen details the rural Hungarian deportations to Auschwitz-Birkenau, back-breaking slave labour in Auschwitz I, the infamous 'death march' of January 1945, the painful aftermath of liberation, and a journey of physical and psychological healing.